How to use evidence-based dental practices to improve your clinical decision-making - Carrasco-Labra, Alonso; Brignardello-Petersen, Romina; Glick, Michael; Azarpazhooh, Amir; Guyatt, Gordon (Practical guide series (American Dental Association), 2020)
This book is a one-stop resource for learning how to harness the power of the latest scientific information and optimize patient care. How to Use Evidence-Based Dental Practices to Improve Your Clinical Decision-Making is the definitive resource for dental students and practitioners who want to learn from leaders in the field of evidence-based dentistry (EBD); quickly conduct searches for the latest research; master the skill of critically appraising clinical studies; confidently apply the latest research to patient care; teach others how to inform their practice with the latest clinical evide.